Effect of Temperature on Soil Corrosion Behavior of X65 Pipeline Steel in Compressor Operation Area - WANG Hong - xin, CHEN Shao - song, YANG Xiao - yan, WANG Shu - jun, CUI Wei (Cailiao Baohu, 2021)
The high temperature environment in the compressor operating area in the compressor station has corrosion effect on the pipeline, resulting in the failure of the pipeline. However, few studies have focused on the corrosion characteristics and behaviors of pipeline in compressor operation area. The corrosion behavior of the pipeline under three ambient temperatures of 70～100 ℃, 40～70 ℃ and 10～30 ℃ in the compressor operating area was studied by means of embedding corrosion coupons, combining with the pipe - to - soil potential test, corrosion morphology, corrosion weight loss analysis and XRD test analysis of corrosion products. The corrosion mechanism of the pipeline under high temperature environment was also discussed. Results showed that the corrosion rate of the self - corrosion coupons and the cathodic protection coupons were higher in the high temperature environment and lower in the low temperature environment. The corrosion rate of cathodic protection coupons was lower than that of self - corrosion coupons. The corrosion of pipeline in high temperature environment could be reduced by improving the cathodic protection of pipeline.